Efficacy and Safety of Switching to Dolutegravir/Lamivudine Versus Continuing a Tenofovir Alafenamide–Based 3- or 4-Drug Regimen for Maintenance of Virologic Suppression in Adults Living With Human Immunodeficiency Virus Type 1: Results Through Week 144 From the Phase 3, Noninferiority TANGO Randomized Trial . (25th January 2022) - Osiyemi, Olayemi; De Wit, Stéphane; Ajana, Faïza; Bisshop, Fiona; Portilla, Joaquín; Routy, Jean Pierre; Wyen, Christoph; Ait-Khaled, Mounir; Leone, Peter; Pappa, Keith A; Wang, Ruolan; Wright, Jonathan; et al.
Abstract: Background: Switching to dolutegravir/lamivudine (DTG/3TC) was noninferior to continuing tenofovir alafenamide (TAF)–based regimens for maintaining virologic suppression at week 48 of the TANGO study. Here we present week 144 outcomes (efficacy, safety, weight, and biomarkers). Methods: TANGO is a randomized (1:1, stratified by baseline third agent class), open-label, noninferiority phase 3 study. Virologically suppressed (>6 months) adults with human immunodeficiency virus type 1 (HIV-1) switched to once-daily DTG/3TC or continued TAF-based regimens. Results: A total of 741 participants received study treatment (DTG/3TC, n = 369; TAF-based regimen, n = 372). At week 144, the proportion of participants with an HIV-1 RNA level ≥50 copies/mL (primary end point, Snapshot; intention-to-treat–exposed population) after switching to DTG/3TC was 0.3% (1 of 369) versus 1.3% (5 of 372) for those continuing TAF-based regimens, demonstrating noninferiority (adjusted treatment difference, −1.1 [95% confidence interval, −2.4 to .2), with DTG/3TC favored in the per-protocol analysis (adjusted treatment difference, −1.1 [−2.3 to −.0]; P = .04). Few participants met confirmed virologic withdrawal criteria (none in the DTG/3TC and 3 in the TAF-based regimen group), with no resistance observed. Drug-related adverse events were more frequent with DTG/3TC (15%; leading to discontinuation in 4%) than TAF-based regimens (5%; leading to discontinuation in 1%) through week 144, but rates were comparable after week 48 (4%; leading to discontinuation in 1% in both groups). Changes from baseline in lipid values generally favored DTG/3TC; no clinical impact on renal function and comparable changes in inflammatory and bone biomarkers across groups were observed. Conclusions: Switching to DTG/3TC demonstrated noninferior and durable efficacy compared with continuing TAF-based regimens in treatment-experienced adults with HIV-1, with good safety and tolerability, and no resistance through 144 weeks. Video Abstract: Abstract : Switching to dolutegravir/lamivudine (DTG/3TC), versus continuing tenofovir alafenamide–based regimens, showed durable efficacy and safety through 144 weeks, with no virologic failure or resistance detected, supporting the use of DTG/3TC in virologically suppressed individuals with human immunodeficiency virus type 1.